2017
DOI: 10.6113/jpe.2017.17.3.811
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Intermittent Life Testing Program for IGBT

Abstract: The reliability issue of IGBT is a concern for researchers given the critical role the device plays in the safety of operations of the converter system. The reliability of power devices can be estimated from the intermittent life test, which aims to simulate typical applications in power electronics in an accelerated manner to obtain lifetime data. However, the test is time-consuming, as testing conditions are not well considered and only rough provisions have been made in the current standards. Acceleration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Additionally, a survey based on over 200 products from 80 businesses found that 31% of respondents selected semiconductor-powered devices as the most fragile parts of power converters used for various power applications [11]. Furthermore, many research-ers have emphasized numerous IGBT-module-related research areas and proposed vari-ous techniques and analysis methods for the acceleration testing of these modules to es-timate failure modes in the early stages of the implementation process, such as the analy-sis of IGBT module fault causes presented in [12,13]; the various techniques of accelera-tion testing for fault diagnostic methodologies given in [14][15][16]; the analysis of parameters affecting failure modes in [17]; and the different measuring equipment used in the experimental environment for module fault diagnosis, such as a scanning electron microscope (SEM), X-ray, and an IR camera, as proposed in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a survey based on over 200 products from 80 businesses found that 31% of respondents selected semiconductor-powered devices as the most fragile parts of power converters used for various power applications [11]. Furthermore, many research-ers have emphasized numerous IGBT-module-related research areas and proposed vari-ous techniques and analysis methods for the acceleration testing of these modules to es-timate failure modes in the early stages of the implementation process, such as the analy-sis of IGBT module fault causes presented in [12,13]; the various techniques of accelera-tion testing for fault diagnostic methodologies given in [14][15][16]; the analysis of parameters affecting failure modes in [17]; and the different measuring equipment used in the experimental environment for module fault diagnosis, such as a scanning electron microscope (SEM), X-ray, and an IR camera, as proposed in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As the operating temperature of the device increases, the life cycle will be shorter. Therefore, reducing the temperature of the device is an effective way to extend its life cycle [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As power electronic equipment has come into widespread use, insulated gate bipolar transistor (IGBT) fully controlled power electronic devices, combining the facile drive of MOSFET with the low conduction loss of a bipolar junction transistor (BJT), and possess good switching performance, have found wide application in industrial automotive, traction, and solar inverter areas [ 1 , 2 , 3 ]. Therefore, knowing whether an IGBT is in a normal state is critical to the safe operation of the system [ 4 ]. Generally, the performance of a system may gradually decline as IGBTs contain numerous materials with different coefficients of thermal expansion (CTE) with many interfaces, which can wear out and cause overstress failures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%